2014
DOI: 10.1155/2014/960262
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Virtual Touch Tissue Imaging Quantification, a New Shear Wave Velocity Imaging Method, for Breast Lesion Assessment by Ultrasound

Abstract: Objectives. To evaluate virtual touch tissue imaging quantification (VTIQ) as a new elastography method concerning its intra- and interexaminer reliability and its ability to differentiate benign from malignant breast lesions in comparison to and in combination with ultrasound (US) B-mode breast imaging reporting and data system (BI-RADS) assessment. Materials and Methods. US and VTIQ were performed by two examiners in 103 women with 104 lesions. Intra- and interexaminer reliability of VTIQ was assessed. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 29 publications
2
51
0
2
Order By: Relevance
“…To date, only 1 study reported the application of VTIQ for evaluating thyroid nodules, 22 although VTIQ has been shown to be useful and reproducible in accessing breast lesions and other organs. 19,20,32,33 In this study, the SWV parameters in malignant nodules were all higher than those in benign nodules, and the SWV mean showed the highest AUC value among them, with a cutoff value of 2.90 m/s. By comparison, in a previous study, Azizi et al 22 reported that VTIQ showed an AUC of 0.78 with a cutoff value of 3.54 m/s.…”
Section: Discussionmentioning
confidence: 51%
“…To date, only 1 study reported the application of VTIQ for evaluating thyroid nodules, 22 although VTIQ has been shown to be useful and reproducible in accessing breast lesions and other organs. 19,20,32,33 In this study, the SWV parameters in malignant nodules were all higher than those in benign nodules, and the SWV mean showed the highest AUC value among them, with a cutoff value of 2.90 m/s. By comparison, in a previous study, Azizi et al 22 reported that VTIQ showed an AUC of 0.78 with a cutoff value of 3.54 m/s.…”
Section: Discussionmentioning
confidence: 51%
“…The shear wave velocity (SWV) can be measured within the lesion, enabling a quantitative evaluation of tissue elasticity. In contrast to strain elastography, ARFI imaging and SWE do not require manual compression; the quantification is based on an intrinsic tissue property, and thus, it has a high user-independence and reproducibility (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Noninvasive diagnostic measures complementing radiographic mammography are candidates to reduce the number of false‐positive findings triggering invasive procedures in breast cancer screening participants. In terms of screening feasibility, ultrasound elastography and unenhanced abbreviated breast magnetic resonance imaging (MRI) currently appear to have potential for added benefit during noninvasive work‐up . Recently, contrast‐free breast MRI protocols with high‐quality diffusion‐weighted imaging (DWI) have shown promise in the diagnostic decision‐making of breast lesions .…”
mentioning
confidence: 99%
“…In terms of screening feasibility, ultrasound elastography and unenhanced abbreviated breast magnetic resonance imaging (MRI) currently appear to have potential for added benefit during noninvasive work-up. 5,6 Recently, contrast-free breast MRI protocols with high-quality diffusion-weighted imaging (DWI) have shown promise in the diagnostic decisionmaking of breast lesions. [7][8][9][10][11] The combination of DWI with morphological T 2 -weighted imaging sequences has been reported to provide reliable characterization of breast lesions.…”
mentioning
confidence: 99%